Analysis of the situation of the homosexual minority in South Korea in the 21st century. Case study of the "Merry Queer" program - Burski, Jakub (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The aim of the article is to examine the changing social attitudes towards the homosexual minority in South Korea in the 21st century. It was hypothesized that the image of homosexual people and same-sex couples in South Korean society has warmed in recent years, which may be evidenced by the increased interest in problems common to minorities and the creation of programs and series touching on the issues of same-sex couples. The article aims to answer the research questions: What attitudes of parents towards homosexual children are shown in the media? What are the views on same-sex couples in South Korean society? Has there been an increase in the popularity or number of productions featuring a homosexual theme on TV in recent years? What are the main problems faced by gay people in South Korea? The analysis adopted a qualitative method through the analysis of participants' behavior and comments in relation to the program and a quantitative method as an analysis of statistics. The basis of the analysis is the "Merry Queer" program, especially the problems affecting homosexual people in the family and Korean society itself, as well as its social reception and public opinion polls on the homosexual minority in South Korea in the period of 2001-2021, with particular importance here are polls by the Gallup Korea Research Institute and the Korean Statistical Information Service. The development and increase in the number of productions with a homosexual theme were also examined.